Multiscale Traffic Flow Modeling in Mixed Networks. Issue 1 (January 2014) - Joueiai, Mahtab; van Lint, Hans; Hoogendoom, Serge P.
Multiscale traffic flow modeling, which combines traffic models of different scales (e.g., of network and traffic representation), offers many opportunities for the simulation and evaluation of traffic measures and policies in large networks. For example, macroscopic continuum models of traffic flow could be used to simulate the propagation of traffic on large freeway corridors and networks efficiently and parsimoniously, whereas microscopic models of traffic flow could be used to simulate those parts of the network where more detail (e.g., lateral behavior) is required, such as at intersections and toll plazas. One key requirement of such a multiscale framework is related to the interface between models of different scales. This interface should ensure consistency in (a) vehicle conservation and (b) vehicle and traveler properties that must be transported over this interface (e.g., vehicle type, occupancy, and destination). In the approach presented, both types of consistency problems can be solved simultaneously, and this approach is illustrated with an integrated example. This multiscale modeling framework enables the coupling of any macroscopic model with any microscopic model (and vice versa) without putting constraints on the internal structure or parameterization in either model.